2005
DOI: 10.1049/el:20050892
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potential actuated brain computer interface: a brain-actuated cursor system

Abstract: Flash visual evoked potential (FVEP), induced by OFF-to-ON flash, i.e. flash onset, in a light emitting diode (LED) was used to control four cursor movements (left, right, up, down), and left-and rightbutton clicks on a screen menu. ON or OFF duration in each flashing sequence was designed to be random so that all flashing sequences were mutually independent. Since FVEPs are time-locked and phaselocked to flash onsets of gazed LEDs, segmenting EEG signals based on the flash onsets of each flashing sequence fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…58,59 Accordingly, some research groups are engaging themselves in developing exogenous BCIs for faster ITRs, such as visual evoked potential (VEP)-based BCI systems. 6,[25][26][27] VEP has been reported as a stable response in EEG measurements, which has been used to monitor anesthesia level during surgery, 41,55 to diagnose prechiasmal and retrochiasmal lesions, 5,23,32,57 to indicate intracranial pressure induced by a head injury, 36 and to alarm brain death. 42,54 Due to the neural connections and interactions of the route from the retina to the primary visual cortex, VEP is time-locked and phaselocked to the onset of visual stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…58,59 Accordingly, some research groups are engaging themselves in developing exogenous BCIs for faster ITRs, such as visual evoked potential (VEP)-based BCI systems. 6,[25][26][27] VEP has been reported as a stable response in EEG measurements, which has been used to monitor anesthesia level during surgery, 41,55 to diagnose prechiasmal and retrochiasmal lesions, 5,23,32,57 to indicate intracranial pressure induced by a head injury, 36 and to alarm brain death. 42,54 Due to the neural connections and interactions of the route from the retina to the primary visual cortex, VEP is time-locked and phaselocked to the onset of visual stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…FVEP can be measured in patients who have very poor visual acuity (Spehlmann, 1985), and some studies also reported that the FVEP can be measured in patients who can see flashes clearly but not pattern stimuli owing to their partial deficiencies in optical fiber connections between retina and visual cortex (Kriss et al, 1982;Wilson, 1978). These studies suggest that the FVEP is a widely measurable biosignal which has also been used as a control signal for BCI systems (Lee et al, 2005;Lee et al, 2006;Sutter, 1992). The visual 'Flash offset' responses have been investigated in the single-neuron recording (Duysens et al, 1996;Brooks & Huber , 1972) and electroretinogram (ERG) (Kondo et al, 1998) studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the velocities of eye saccade can be up to 700°/sec within a duration as short as 20ms (Carpenter, 1988), and thereby most video-based eye trackers are equipped with costly high-speed video capture systems (>250 Hz) (Duchowski, 2003). In contrast, the VEP-based BCI aims to develop a user-friendly and low-cost system but with the compromised response time of 1 ~ 4 seconds (Cheng et al, 2002;Cheng et al, 2006;Kelly et al, 2005;Lee et al, 2005;Lee et al, 2006;Middendorf et al, 2000;Sutter 1992;Trejo et al, 2006), which requires only an EEG and an EOG channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the drawback of this control signal is that the user has to keep his eyes fixed at one point bereft of any random movement. Lee et al [45][46][47] exposed the subjects (participants of the experiment) with a 5 × 5 matrix that contained flashing stimuli of digits, characters, and symbols displayed on the LCD screen. The cells of the matrix flicker in a random sequence.…”
Section: Visually Evoked Potentialsmentioning
confidence: 99%